1984
DOI: 10.1002/bip.360230509
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational analysis of peptides, polypeptides, and proteins. XVIII. Conformational sensitivity of the α‐helix spectrum: αI‐ and αII‐Poly(L‐alanine)

Abstract: SynopsisThe q -h e l i x (6 = -70,47O, $ = -35.75O) is a structure having the same n and h as the (standard) aI-helix (4 = -57.37", $ = -47.49'). Its conformational angles are commonly found in proteins. Using an improved a-helix force field, we have compared the vibrational frequencies of these two structures. Despite the small conformational differences, there are significant predicted differences in frequencies, particularly in the amide A, amide I, and amide I1 bands, and in the conformation-sensitive regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 36 publications
(6 reference statements)
11
73
0
Order By: Relevance
“…The lipid SM was not used because it has a strong signal in the amide I region, but the results in the functional assays were similar when using liposomes with or without SM. Our assignment of the different secondary structures was the same as that described previously (15)(16)(17)(18)(19)(20). The data revealed that the peptide adopts predominantly distorted/dynamic helical structures in both types of lipids ( Fig.…”
Section: Anticancer Activity Insupporting
confidence: 74%
“…The lipid SM was not used because it has a strong signal in the amide I region, but the results in the functional assays were similar when using liposomes with or without SM. Our assignment of the different secondary structures was the same as that described previously (15)(16)(17)(18)(19)(20). The data revealed that the peptide adopts predominantly distorted/dynamic helical structures in both types of lipids ( Fig.…”
Section: Anticancer Activity Insupporting
confidence: 74%
“…In support of this, the amide I region from 1656 to 1670 cm Ϫ1 is characteristic of a 3 10 -helix or dynamic/distorted ␣-helix, as was previously suggested in a study that examined the structural changes in phospholipase A 2 (69). The assignment of the amide I region from 1656 to 1670 cm Ϫ1 to the dynamic helix is further supported by studies that examined distorted ␣-helical structures (a II -helices) in bacteriorhodopsin and other proteins (70,71). Similar structures were reported previously for a model amphipathic ␣-helical peptide and its diastereomer (25).…”
Section: Resultssupporting
confidence: 54%
“…The amide I region from 1656 to 1670 cm Ϫ1 is characteristic of 3 10 -helix or dynamic/distorted ␣-helix, as was previously suggested in a study that examined structural changes in phospholipase A 2 (48). The assignment of the amide I region from 1656 to 1670 cm Ϫ1 to dynamic helix is further supported by studies that examined distorted ␣-helical structures (␣ II -helices) in bacteriorhodopsin and other proteins (49,50). These studies demonstrated that distorted ␣-helical structures are characterized by increased amide I frequencies.…”
Section: Figsupporting
confidence: 65%